Analysis Of The Influence Of Science In Science Learning In Class V Sds Bina Satria Mulia - Afifah, Cut Fatima Nur; Azzahra, Tsabitah Humairah (Journal of Innovation in Research, Education and Culture (JIREC), 2023)
The formulation of the research problem is as follows :